Adverse Effects of Topiramate - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effectiveness and safety of topiramate in 87 children with intractable epilepsy treated at three Canadian Centers were evaluated at the IWK-Grace Health Centre, Halifax, NS, Canada.